UTILISATION OF RICE HUSK ASH FOR IMPROVEMENT OF DEFICIENT SOILS IN NIGERIA: A REVIEW (Nigerian Journal of Technology, 2017)
Review of studies, mostly carried out at laboratory scale, on the utilisation of Rice Husk Ash (RHA) for improvement of deficient soils in Nigeria is presented. Although, few studies have focused on using the RHA as soil improving additive alone, most of the studies have been on its usage as additive to the conventional soil stabilizers (cement and lime). The studies generally showed improvement in the geotechnical properties of soils, either modified or stabilised with the ash, thus indicating the potentials of using this agricultural waste for improvement of geotechnical properties of deficient soils. This suggest that using this material at large scale level in geotechnical engineering practice will help in the provision of stable and durable geotechnical structures, reduce cost of soil improvement and the environmental nuisance caused by the unused waste. This will considerably add to the economic value chain of rice farmers/producers in Nigeria.http://dx.doi.org/10.4314/njt.v36i2.10